How are indigenous students' perceptions of mathematics learning based on the ethnomathematics of the Nias community? - Gee, Efrata; Turmudi, Turmudi; Priatna, Nanang; Priatna, Bambang Avip (Universitas Islam Negeri Raden Intan Lampung, 2026)
Ethnomathematics is widely recognized as an approach that connects mathematics learning with students' cultural experiences. However, previous studies have mainly identified mathematical concepts in cultural practices and developed ethnomathematics-based materials, while indigenous students' perceptions remain underexplored. This study analyzed indigenous students' perceptions of ethnomathematics-based mathematics learning in the context of Nias culture. A descriptive mixed-methods design was conducted with seventh-grade indigenous students at a junior high school in South Nias, Indonesia. Data were collected through a perception questionnaire and semi-structured interviews and analyzed using descriptive statistics and thematic analysis. Results showed that students' perceptions were generally adequate. The absorption, understanding, and evaluation dimensions scored 74.73%, 70.57%, and 69.89%, respectively. Although students appreciated the cultural contexts used in learning, many struggled to relate cultural practices and artifacts to formal mathematical concepts, indicating that cultural familiarity alone does not ensure meaningful understanding. These findings suggest that ethnomathematics instruction should integrate cultural contexts with appropriate pedagogical support to help indigenous students transform cultural knowledge into formal mathematical understanding.